2008
DOI: 10.1057/palgrave.jors.2602347
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning maps for decision aid: an integrated approach for problem-structuring and multi-criteria evaluation

Abstract: This paper proposes a tool for multi-criteria decision aid to be referred to as a reasoning map. It is motivated by a desire to provide an integrated approach to problem structuring and evaluation, and in particular, to make the transition between these two processes a natural and seamless progression. The approach has two phases. In the first one, the building of a reasoning map supports problem structuring, capturing a decision maker's reasoning as a network of means and ends concepts. In the second phase, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 30 publications
0
73
0
12
Order By: Relevance
“…Previous work (Belton et al, 1997;Bana e Costa et al, 1999;Montibeller et al, 2008) has shown that mapping-based PSMs can be helpful for this purpose. On the other hand, Daellenbach (1997) proposed the use of MCDA to bring about compromise solutions at one of the stages of SSM, whereas Petkov at al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work (Belton et al, 1997;Bana e Costa et al, 1999;Montibeller et al, 2008) has shown that mapping-based PSMs can be helpful for this purpose. On the other hand, Daellenbach (1997) proposed the use of MCDA to bring about compromise solutions at one of the stages of SSM, whereas Petkov at al.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the approach is presented in Montibeller et al (2007a) and examples of its use in supporting real-world decision-making processes can be found in Montibeller et al (2007a;2007b).…”
Section: Reasoning Mapsmentioning
confidence: 99%
“…In a Reasoning Map, the strength of perceived influence seeks to capture, in qualitative terms, the decision-makers' perception of the extent to which an increase in the performance of an action on a means concept may lead to an increase in its performance on an end concept. However, it should be recognised that, no matter how theoretically well-defined the model is, it is always difficult, in practice, to make sure that decision-makers use the pre-defined theoretical framework consistently throughout the process (see Montibeller et al, 2007a).…”
Section: The Means-ends Networkmentioning
confidence: 99%
See 2 more Smart Citations